Green nanocomposite for the adsorption of toxic dyes removal from colored waters - Akbar, Ishaa; Hanif, Muhammad Asif; Rashid, Umer; Bhatti, Ijaz Ahmad; Rais Ahmad Khan; Kazerooni, Elham Ahmed (Multidisciplinary Digital Publishing Institute, 2022)
The discharge of dyes from textile industries led to a broad range of toxicological and environmental effects, posing severe health issues for humans and animals worldwide. These dyes are highly stable and, if not adequately treated, remain in the environment for extended periods. Adsorption, the most efficient and cost-effective method, offers unique advantages for using natural adsorbents, such as marble waste composites, for dye removal. The easy availability of marble waste, its low cost, its eco-friendly nature, its ease of operation, its simplicity of design, its flexibility, and its great affinity for dyes make it a suitable option for dye removal. Golden marble waste nanocomposites are prepared for dye removal. The results from the studies suggested that treated golden marble composite materials exhibit better adsorption efficiency (224.8, 299.5, and 369.2 mg/g) for adsorptive removal of dyes than untreated golden marble composite materials (114.4 mg/g). This research also used isothermic and kinetic models to evaluate the effects of numerous parameters, for example, the initial dye concentration, pH, time, temperature, and adsorbent dose. The highest removal of 369.9 mg/g was achieved during the present study for blue dye at an optimized pH of 7 and a temperature of 30 °C. It was observed that golden marble waste composites gave better R2 (0.99) values for second-order kinetics in the kinetic model. Results obtained from comparing Langmuir, Freundlich, Temkin, Dubinin, and Herkin Jura isotherms showed that the R2 values of the Langmuir isotherm for Foron red (0.97), the Temkin isotherm for Foron blue (0.98), and the Freundlich isotherm for Foron black dye (0.97) fit on adsorption for both treated and untreated composites. Characterization techniques, such as scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), are also discussed for the structural determination of golden marble waste composites.